Bis(1-benzylpiperazine-1,4-diium) hexachloridocadmate(II) dihydrate - El Glaoui, Meher (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, (C(11)H(18)N(2))(2)[CdCl(6)]·2H(2)O, consists of one 1-benzylpiperazine-1,4-diium dication, one water molecule and one-half of a [CdCl(6)](4−) anion, located on an inversion centre. The crystal packing is governed by an extensive three-dimensional network of intermolecular O—H⋯Cl, C—H⋯Cl, N—H⋯O and N—H⋯Cl hydrogen bonds, two of them bifurcated.